2016
DOI: 10.1111/sltb.12304
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Connections Between Eating Disorder Symptoms, Perceived Burdensomeness, Thwarted Belongingness, and Suicide Risk Among Undergraduate Students

Abstract: Suicide attempts and premature mortality due to suicide are elevated in people with eating disorders. Informed by the interpersonal theory of suicide, two studies examined the role of perceived burdensomeness and thwarted belongingness in explaining the association between eating disorder symptoms and suicide risk. Results indicated that various eating disorder symptoms had an indirect effect on suicide risk through perceived burdensomeness and thwarted belongingness. Targeting perceived burdensomeness and thw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
(47 reference statements)
0
23
1
Order By: Relevance
“…Additional research has found that general eating psychopathology is related to suicide risk through both perceived burdensomeness and thwarted belongingness (Dodd, Smith, & Bodell, 2014;Kwan, Gordon, Carter, Minnich, & Grossman, 2017). Additional research has found that general eating psychopathology is related to suicide risk through both perceived burdensomeness and thwarted belongingness (Dodd, Smith, & Bodell, 2014;Kwan, Gordon, Carter, Minnich, & Grossman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has found that general eating psychopathology is related to suicide risk through both perceived burdensomeness and thwarted belongingness (Dodd, Smith, & Bodell, 2014;Kwan, Gordon, Carter, Minnich, & Grossman, 2017). Additional research has found that general eating psychopathology is related to suicide risk through both perceived burdensomeness and thwarted belongingness (Dodd, Smith, & Bodell, 2014;Kwan, Gordon, Carter, Minnich, & Grossman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Within this model of suicidal behavior, ED behaviors are believed to be painful and provocative experiences that increase pain tolerance and fearlessness about death and thus increase the capability for suicidal behavior. Studies have also found that some ED symptoms are related to suicide ideation through their relationship with burdensomeness and failed belongingness (Forrest et al., ; Kwan, Gordon, Carter, Minnich, & Grossman, ). Therefore, individuals with EDs may be at increased risk for suicide due to elevations in perceived burdensomeness, failed belongingness, and/or capability for suicide.…”
Section: Cross‐sectional Literature On the Association Between Eatingmentioning
confidence: 99%
“…Central to this aim is understanding how risk factors (predictors) differ from other associations (e.g., correlations). According to a prominent risk factor typology (i.e., Kraemer et al, 1997), a correlate is a factor that is associated with another factor; however, the temporal nature of the relation is unclear. Correlates may be identified using cross-sectional methods, but it is impossible to determine which correlate temporally precedes the other.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early work employing the IPTS framework for understanding the ED-suicide relation investigated the role of capability in suicidal behavior among people with EDs. Given work demonstrating that people with EDs have elevated pain tolerance (Lautenbacher, Pauls, Strian, Pirke, & Krieg, 1990;Strigo et al, 2013), researchers hypothesized that ED behaviors may serve as the distressing or painful behaviors by which habituation to pain and fear occur. This hypothesis has been partially supported: over-exercise, vomiting, laxative use, and restriction are associated with capability for suicide Witte, Didie, Menard, & Phillips, 2012).…”
mentioning
confidence: 99%